2009
DOI: 10.1111/j.1540-8159.2008.02285.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Benefit of Multiple Programmable Pacing Configurations in Patients with Biventricular Pacemakers

Abstract: Changing the LVS configuration changes hemodynamic function in some CRT system recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…These findings tally with those obtained in two previous studies. 16,17 The first one, carried out in 14 patients, found significant differences between four and six possible configurations in the CO (4.6 ± 1.4 L/min vs 3.9 ± 1.4 L/min; P < 0.001) and myocardial performance index (0.40 ± 0.29 vs 0.64 ± 0.48; P = 0.003). 16 The second study, carried out in 19 patients with a quadripolar lead, found significant acute hemodynamic differences, determined by invasive estimation of dP/dt max between the best and worst pacing vector.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These findings tally with those obtained in two previous studies. 16,17 The first one, carried out in 14 patients, found significant differences between four and six possible configurations in the CO (4.6 ± 1.4 L/min vs 3.9 ± 1.4 L/min; P < 0.001) and myocardial performance index (0.40 ± 0.29 vs 0.64 ± 0.48; P = 0.003). 16 The second study, carried out in 19 patients with a quadripolar lead, found significant acute hemodynamic differences, determined by invasive estimation of dP/dt max between the best and worst pacing vector.…”
Section: Discussionmentioning
confidence: 98%
“…16,17 The first one, carried out in 14 patients, found significant differences between four and six possible configurations in the CO (4.6 ± 1.4 L/min vs 3.9 ± 1.4 L/min; P < 0.001) and myocardial performance index (0.40 ± 0.29 vs 0.64 ± 0.48; P = 0.003). 16 The second study, carried out in 19 patients with a quadripolar lead, found significant acute hemodynamic differences, determined by invasive estimation of dP/dt max between the best and worst pacing vector. 17 In the QUARTO study, we observed that in over half of the patients the best CO was obtained with configurations only available with the quadripolar lead ("nontraditional configurations").…”
Section: Discussionmentioning
confidence: 98%